Analisis Disiplin Kerja Terhadap Turn Over Karyawan Bagian Produksi Pada PT.Tomo Food Industri Sumedang - Wulan Ariani Damayanti (Universitas Sebelas April, Fakultas Ekonomi dan Bisnis, 2023)
The problem that occurs at PT.Tomo Food Industri Sumedang is employee turnover which is still high every year, allegedly one of them is caused by employees who are less disciplined. This study aims to determine ; (1) Work discipline of employees in the production division of PT. Tomo Food Industri Sumedang; (2) Turn over of employees in the production division of PT.Tomo Food Industri Sumedang; and (3) is there a significant effect of work discipline on the turnover of production employees at PT. Tomo Food Industri Sumedang. This research is a quantitative research, using primary and secondary data sources and using a questionnaire to determine the data. The population in this study were all employees of the production division at PT.Tomo Food Industri Sumedang, with a total of 50 people. The data of this study used simple regression analysis, correlation test, coefficient of determination and hypothesis testing. The results of this study indicate that work discipline is 1,620 (good enough) with an average of 64.80%, employee turnover is 1,585 (good enough) with anaverage of 63%. Furthermore, the magnitude of the relationship between work discipline and turnover of production employees at PT. Tomo Food Industri Sumedang is 0.875, and the magnitude of the influence of work discipline on employee turnover in the production division of PT. Tomo Food Industri Sumedang is 76.6% and there are 23% other factors. . The results of the calculation of the hypothesis test, it turns out that tcount (12.52) or ttable (1.67722), it can be said that there is a positive influence between work discipline on employee turnover in the production division at PT.Tomo Food, Sumedang industry, which is acceptable. In carrying out work activities, employees who come to work and go home on time, do all their work well, can comply with all company regulations and also applicable social norms can reflect employee comfort which also prevents employees' desire to leave the company.